THE ROLE OF MATERNAL SUPPORT MOTIVATORS AND EXCLUSIVE BREASTFEEDING BEHAVIOR AT THE PUBLIC HEALTH CENTER IN YOGYAKARTA: A CORRELATIONAL STUDY - Aulia Ridla Fauzi; Purnomo Suryantoro; Dewi Rokhanawati (Belitung Raya Foundation, Indonesia, 2018)
Background: The target of exclusive breastfeeding decreased to 17% at the Pakualaman Health Center in Yogyakarta due to the barriers caused by the wrong perception regarding breastfeeding and returning to work. The roles of motivators in the promotion activity and exclusive breastfeeding reinforcements are expected to exchange experience among peers who have experienced of exclusive breastfeeding at maternal group activities. Objective: To identify the correlation between the role of motivators in supporting maternal groups in providing exclusive breastfeeding and exclusive breastfeeding behavior. Methods: This was a correlational study with cross-sectional design on 55 samples selected using purposive sampling technique. This study was conducted in women who had a > 6-23-month infant at Pakualaman Health Center in Yogyakarta Indonesia in 2017. Chi-square and multiple logistic regressions were used for data analysis. Results: There was no significant correlation between the role of motivators in supporting maternal groups and exclusive breastfeeding behavior in mothers with 0-6-month infants (p= 0.631). There was a significant correlation between the variable of access to information with the behavior of exclusive breastfeeding (p = 0.019). Conclusion: The role of motivators in supporting maternal groups has no significant relationship with exclusive breastfeeding behavior. It is suggested for midwives to increase the access of information among mothers, as information access has significant association with behavior of mothers in exclusive breastfeeding.